Pengembangan LKPD Berbasis RME Materi Pengukuran Konteks Makanan Olahan Durian Untuk Meningkatkan Hasil Belajar Siswa Matematika Siswa Kelas IV SD - Fitri Yanti , Balida Luvitasari; Susanta, Agus; Juarsa, Osa (Jurnal Kajian Pendidikan Dasar, 2025)
This study aimed to create Student Worksheets (LKPD) based on the Realistic Mathematics Education (RME) approach to enhance students' cognitive mathematics learning outcomes, focusing on weight and volume measurement using standard and non-standard units. Utilizing the Research and Development (R&D) method, the Four-D (4D) model—define, design, develop, disseminate—guided the process. Quantitative data from expert validators' rating scale questionnaires and qualitative feedback through comments shaped the development. The LKPD adhered to RME steps: understanding contextual problems, explaining these issues, solving them, comparing answers, and drawing conclusions. Expert validation determined the LKPD's feasibility with scores of 0.67 for content, 0.83 for language, and 0.92 for design. Students displayed a 95% satisfaction rate, demonstrating the LKPD's efficacy. Pre-test and post-test scores improved from 6.17 to 8.10, respectively. The N-Gain test highlighted cognitive growth at level C3 (79%), level C4 (75%), and level C5 (74%). This development shows the potential of the RME-based approach in strengthening students' understanding and engagement in mathematics.